(1256) An exact Branch-and-Bound procedure for the quadratic assignment problem إجراء دقيق للتفرع والتقييد لمسألة التخصيص التربيعي - Bazaraa, Mokhtar S.; Elshafei, Alwalid N. (The Institute Of National Planning., 2018)
The quadratic-assignment problem is a difficult combinatorial problem which still remains unsolved. In this study, an exact branch-and-bound procedure, which is able to produce optimal solutions for problems with twelve facilities or less, is developed. The method incorporates the concept of stepped fathoming to reduce the effort expended in searching the decision trees, computational experience with the procedure is presented.